(untitled) (Mugda Medical College Journal, 2023)
Background: Vesicovaginal fistula (VVF) is a significant cause of physical & psychological disability with social stigmatization especially in low- and middle-income countries. Over 80% of such cases result from neglected prolonged and obstructed labour. Objective: The purpose of the study was to observe the outcome of transvaginal local repair of vesicovaginal fistula (VVF). Methods: This descriptive study was carried out at the Department of Obstetrics & Gynaecology, Sylhet M.A.G. Osmani Medical College Hospital, Bangladesh, from July 2007 to June 2008, on 50 patients of vesicovaginal fistula. We included women who were suffering from VVF and who were operated before and diagnosed as a failed repair of VVF. We excluded those patients who had VVF with associated problem like rectovaginal fistula (RVF), any repair through transabdominal route and unwilling to take part in this study. Before surgery, each woman was assessed by medical and surgical history, examination and necessary investigations. Typically, regional anesthesia was utilized for the fistula surgery. However, general anesthesia was given when required. During surgery, transvaginal approach was taken for repair. The vagina was packed for haemostasis. Vaginal pack was removed after 1-2 days depending on instruction of the surgeon. Repacking of vagina was also done sometimes when there was some leaking during post-operative period. Few patients developed severe constipation post operatively. Results: The participants aged between 16 and 70 years. Among them, majority of the patient belongs to the age 31-35 years (26%) followed by 2nd common group 26-30 years of age (20%) and 3rd one in between 21-25 years of age (16%). Among them 44% patients were primipara and 22% patients were grand multipara. The mobilization during operation was excellent in 30%, satisfactory 64% cases and not enough in 6% cases. After mobilization fistula closed in double layer in 10% and in single layer 90% cases, labial fat graft was given 38% and peritoneal graft was given in 2% cases. During operation bleeding was minimum in 92% cases and in 34% cases catheter was block, urine leakage occurred in 30% cases. Among all patients 14% suffered from fever postoperatively. There was vaginal discharge in 10% cases and UTI in 12%cases which was evidenced by urine culture. Operation was fully successful in 60 percent cases, urethral incontinence in 22% cases & failed in 18% women. Conclusion: In this study, majority of the transvaginal local repair of VVF operations were successful; however, few difficult cases were observed. Mugda Med Coll J. 2023; 6(1): 25-29